Effects of Different Cell Types on Exosome Secretion in 2D Cell Cultures - Thi Trang Uyen, Than; Huyen, Nguyen Thu (VNU Journal of Science: Natural Sciences and Technology; Vol 42 No 2DO - 10.25073/2588-1140/vnunst.5811, 2026)
Exosomes are attracting significant attention as their potential therapeutic agents and have the ability to deliver bioactive molecules in a targeted manner. They have roles in regenerative medicine, neurological disorders, cardiovascular diseases, and immunomodulation. However, the biological activities of exosomes depend on their cargos and are affected by the secreting cells. This study aims to investigate the number and size distribution of exosomes released by Human Exfoliated Deciduous Teeth Stem Cells (SHEDs), fibroblasts, and Umbilical Cord-Derived Mesenchymal Stem Cells (UCMSCs). Additionally, we evaluated the expression of several growth factors in exosomes. The results showed that three different cell types released different numbers of exosomes, with the greatest number belonging to UCMSCs. Additionally, exosome particles from all three samples concentrated at peak 130 nm - 180 nm, and more than 90% of the detected particles ranged from 30 nm to 350 nm. Furthermore, expression levels of growth factors, including Fibroblast Growth Factor-2 (FGF-2), Hepatocyte Growth Factor (HGF), Platelet-Derived Growth Factor-BB (PDGF-BB), and Vascular Endothelial Growth Factor-A (VEGF-A) are different. Growth factors seemed to be more enriched in exosomes derived from UCMSCs and fibroblasts than SHEDs. Data from this study indicate that the characteristics and further application of exosomes were affected by the secreting cell types.